Attractiveness of different citrus pulps to the leaf-cutting ant atta sexdens rubropilosa (Hymenoptera: Formicidae) - Carlos, Amanda A. [UNESP]; Forti, Luiz Carlos [UNESP]; Camargo, Roberto S. [UNESP]; Moreira, Sinara Maria [UNESP]; Verza, Sandra S. [UNESP]; Diniz, Eduardo Arrivabene [UNESP] (My University, 2009)
The most common control method uses toxic baits consisted of dehydrated citrus pulp as carrier and attractant. However, the portion of the citrus fruit that is attractive to ants is still unknown, despite its importance in chemical control. This study compared the attractiveness of different fruit parts of citrus pulps to Atta sexdens rubropilosa workers. Three treatments: pellets of industrial citrus pulp, albedo (mesocarp), and whole citrus pulp were offered randomly to ants and the removal of these substrates by workers was observed. The three pulps were equally attractive to this species (F = 0.8033; p = 0.4633). Although the whole pulp included the epicarp, it was as attractive as the other treatments, possibly because, the material was heated during processing, eliminating any volatile substance that could repel ants.
Keywords: Atta sexdens; Attractiveness; Citrus pulp; Leaf-cutting ants